A Survey On Meteorological Data Analysis Using Data Mining Techniques - Mayilvaganan, M; Vanitha, P (International Journal of Computer Sciences and Engineering, 2015)
Meteorological data analysis in form of data mining is concerned to predict the knowledge of weather condition. To make an accurate prediction is one of the challenging of meteorologist to survey the weather condition efficiently. Rainfall prediction becomes an important issue in agricultural country like India. The atmospheric correlations play a significant role in determining the climate trends which are crucial in understanding the short and long-term trends in climate. The climate changes, so experienced today are mainly due to over ambitious strategies and actions of human being on the eco-system. In this paper, a survey of meteorological data analysis in various data mining techniques is presented. It can be provided for future direction for research.